Work related musculoskeletal disorders among hospital nurses in rural Maharashtra, India: a multi centre survey - Anap, Deepak B.; Iyer, Chandra; Rao, Keerthi (International Journal of Research in Medical Sciences, 2017)
Nurses have one of the highest rates of MSD of any occupation. Although en number of studies were done to find out prevalence of Work related musculoskeletal disorders (WMSDs) among nurses across the world, there is limited information on its prevalence in Rural Maharashtra. This study investigated prevalence of WMSDs, job risk factors and the coping strategies towards reducing the risk of development of WMSDs among nurses from selected hospitals in rural Maharashtra, India. Validated questionnaires were distributed to 250 nurses working rural hospitals across Maharashtra but only 228 questionnaires were returned and 212 complete questionnaires were included for study. On Analysis we found that 89.1% nurses had experienced work-related musculoskeletal pain or discomfort at sometime in their occupational lives. WMSDs was highest in the low back (48.2%), followed by the shoulder (34.6%), neck (33.1) and knee (29 %). Other regions with less prevalence were Thoracic (10.5%), Feet and ankle (7.6%), Elbow ( 1.88%) and Hip (1.6 %). Priority was given to getting help to handle heavy patients ( 57.1 %), nursing procedure modification in order to avoid stress injury ( 50.2 %) coping strategies. Our study Concluded that high prevalence of LBP, Shoulder, neck and Knee pain over a 12-month period among nurses working in Rural hospitals in Maharashtra state , and certain risk factors like working in same position for long time, bending, twisting, lifting and treating excessive number of patients were strongly associated with WMSDs.